Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic markers of COVID-19 irrespective of patients immunosuppression status: a case-control retrospective single-center study - Amalia Papanikolopoulou; Eftychia Eirini Maria Gourdoupari; Polyxeni Alexiou; Charalampos Charalampous; Vasiliki Rapti; Maria Effrosyni Livanou; Eleni Kakalou; Vissaria Sakka; Konstantinos N Syrigos; Garyfallia Poulakou (Journal of Global Antimicrobial Resistance)
AIM: To identify hematological indicators as prognostic tools in hospitalized patients with COVID-19 pneumonia, with or without immunosuppression. BACKGROUND: COVID-19 is often accompanied by severe inflammation and changes in biochemical and hematological parameters. NLR and PLR could have prognostic potential in SARS-CoV-2 infection. METHODS: We retrospectively analyzed patients with COVID-19 pneumonia, sequentially admitted to our Infectious Diseases Department, from June 2021 to December 2022, after the implementation of massive SARS-CoV-2 vaccination programs in Greece. Hospitalized patients were divided in two cohorts according to immunosuppression status, using a propensity score-matching in 1:2 ratio. RESULTS: In total 393 from 400 collected patients (n=131, 33.3% immunocompromised with prior medical history of either hematological malignancy or autoimmune condition and n=262, 66.7% non-immunocompromised) were enrolled: male: n=199(50.6%); mean age 64.7 (SD=16.1) (Table1). According to WHO criteria most of the patients (n=211, 54%) had severe COVID-19 and were vaccinated against COVID-19 (n=209, 53.9%). Median duration of hospitalization was significantly higher in immunocompromised patients [10, IQR (7-16), p=0.036], while intubation and survival weren't significantly different between two groups (p=0.972, 0.756 respectively) (Figure 1). Biochemical and hematological parameters on day 1 and 4 of hospitalization weren't significantly different between two groups (Table 2). In contrast higher NLR values on day 1 were observed for Omicron variant and higher NLR and PLR values on day 1 and 4 for severe COVID-19 (Table 3). CONCLUSIONS: During the 3rd and 4th pandemic wave, NLR and PLR values display promising prognostic markers, irrespective of immunosuppression status, of COVID-19 hospitalized patients.